2018
DOI: 10.5943/mycosphere/9/4/10
|View full text |Cite|
|
Sign up to set email alerts
|

Biodiversity and ecology of lichens of Katmai and Lake Clark National Parks and Preserves, Alaska

Abstract: We inventoried lichens in Lake Clark (LACL) and Katmai (KATM) National Parks and Preserves. We assembled the known information on lichens in these parks by combining field, herbarium, and literature studies. Our results provide baseline data on lichen occurrence that may be used in resource condition assessments, vulnerability assessments, long-term ecological monitoring, and resource management. We report a total of 896 taxa of lichenized fungi from the Parks, adding 889 taxa to the total of seven taxa report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…To compare lichen composition of different areas, we constructed Venn diagrams using the R packages venn () and VennDiagram (Chen & Boutros 2011). We used species lists from McCune et al (2018) for Katmai and Lake Clark National Parks and Preserves, and Spribille et al (2010) for Klondike Gold Rush National Historical Park. Species lists were synonymized based on comparison of the application of names in the four studies and final reported numbers differ slightly from those in the original publications owing to deduplication of names in McCune et al (2018) and follow-up studies since Spribille et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…To compare lichen composition of different areas, we constructed Venn diagrams using the R packages venn () and VennDiagram (Chen & Boutros 2011). We used species lists from McCune et al (2018) for Katmai and Lake Clark National Parks and Preserves, and Spribille et al (2010) for Klondike Gold Rush National Historical Park. Species lists were synonymized based on comparison of the application of names in the four studies and final reported numbers differ slightly from those in the original publications owing to deduplication of names in McCune et al (2018) and follow-up studies since Spribille et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the reports from Kenai Fjords, we include in a separate section at the end of the list of taxa, supplemental information for 14 taxa from nearby Katmai and Lake Clark National Parks, beyond that provided by McCune et al (2018).…”
Section: Resultsmentioning
confidence: 99%
“…The most comprehensive studies of lichen diversity near Kenai Fjords National Park are McCune et al (2018) from Katmai and Lake Clark National Parks, Spribille et al (2010) from Klondike Gold Rush National Historic Park, and forthcoming studies from Glacier Bay National Park (Spribille et al 2020). North and east of the study area Stehn et al (2015) compiled a list of lichens of the Denali National Park region.…”
Section: Introductionmentioning
confidence: 99%
“…Yet it is fair to say that the strict application of temporal banding in lichenology has so far received little support (but see McCune et al 2018). In an extended rebuttal entitled 'Stop the abuse of time!…”
Section: Discussionmentioning
confidence: 99%